2011
DOI: 10.1007/s10157-011-0435-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-glomerular basement membrane (anti-GBM) disease accompanied by vasculitis that was not positive for antineutrophil cytoplasmic antibodies to myeloperoxidase and proteinase 3: a report of two cases and the incidence of anti-GBM disease at one institution

Abstract: The incidence of anti-GBM disease was very low, and our patients were categorized into two groups (Groups I and II) based on whether or not they were positive for MPO- or PR3-ANCA. Two patients in Group II were found to have vasculitis. According to our results, we concluded that the anti-GBM disease of Group II could also be associated with vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For example, incidence figures from the literature are variable. Table 3 summarizes the results of prior studies that have described the incidence of anti-GBM disease (8)(9)(10)(11)(12)(13)(14)(15). Although there may be natural variation in disease rates among the populations studied, obvious differences in study methods may account for the different figures reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, incidence figures from the literature are variable. Table 3 summarizes the results of prior studies that have described the incidence of anti-GBM disease (8)(9)(10)(11)(12)(13)(14)(15). Although there may be natural variation in disease rates among the populations studied, obvious differences in study methods may account for the different figures reported.…”
Section: Discussionmentioning
confidence: 99%
“…Although there may be natural variation in disease rates among the populations studied, obvious differences in study methods may account for the different figures reported. In half of these studies, an incidence rate could not be calculated because the population at risk was not specified (12,13,15) or could only be estimated (11). Studies of renal biopsy registries have reported comparatively lower incidence rates of approximately 0.6 pmp per year (10,14).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-GBM disease is caused by autoantibody against glomerular and alveolar basement membrane, and is pathologically distinct from arteritis [1]. However, anti-GBM disease accompanied by arteritis was reported soon after the establishment of the concept of anti-GBM disease [2,3], and after the generalization of ANCA assay, a substantial proportion (21.2-45.8%) of anti-GBM disease has been found to be positive for ANCA (Table 1) [4][5][6][7][8][9][10][11]. Therefore, ANCA is supposed to be responsible for the arteritis accompanied anti-GBM disease, and ANCA-positive anti-GBM disease is termed ''double positive'' disease.…”
Section: Introductionmentioning
confidence: 99%